Bargaining Sectoral Standards: Towards Canadian Fair Pay Agreement Legislation - Slinn, Sara; Rowlinson, Mark (Windsor Yearbook of Access to Justice / Recueil annuel de Windsor d'accès à la justice)

(untitled) (Faculty of Law, University of Windsor, 2023)
In response to the need for more inclusive collective bargaining legislation to combat inequality and improve conditions in the workplace, this paper considers the recently introduced New Zealand Fair Pay Agreement [FPA] sectoral bargaining framework and offers a preliminary series of ideas and proposals setting out how an FPA model for bargaining sectoral standards could work in Canada. It is intended as the beginning of a more detailed discussion on the development of an FPA regime culminating in model legislation that could be adapted to different Canadian jurisdictions. Guided by principles of accountability, integration, and inclusivity, this proposal is intended to apply to all workers in an employment relationship – including dependent contractors and gig and platform workers. The proposed system is to be structured as a new, stand-alone statute, drawing upon existing institutions administering collective bargaining legislation, incorporating some familiar collective bargaining concepts: good faith bargaining, dues check-off, and unfair labour practice protection. It is intended to preserve existing collective bargaining arrangements by excluding specified sectors with existing high union density or existing sectoral bargaining. However, it is also intended to offer a new, sectoral bargaining option based on industry or occupation sectors, producing FPA “sector agreements” containing minimum standards applying to all employees and employers in the sector. This proposed framework would operate in parallel and in conjunction with the existing enterprise-level collective bargaining system.